Protective Effects of 18β-Glycyrrhetinic Acid on Monocrotaline-Induced Pulmonary Arterial Hypertension in Rats - Zhang, Min; Chang, Zhi; Zhao, Fang; Zhang, Peng; Hao, Yin-Ju; Yan, Lin; Liu, Ning; Wang, Jun-Li; Bo, Lei; Ma, Ping; Zhou, Wei; Ma, Xuan; et al. (Frontiers in Pharmacology, 2019)
Pulmonary arterial hypertension (PAH) is a destructive and rare disorder characterized by a progressive increase in pulmonary artery pressure and vasoconstriction, ultimately leading to right ventricular failure and death. 18β-Glycyrrhetinic acid (18β-GA) is an active ingredient in the commonly used Chinese herbal medicine radix glycyrrhizae, and it possesses antioxidant, anti-inflammatory, anti-tumor, and other pharmacological properties. This study aimed to determine whether 18β-GA has protective effects against monocrotaline (MCT)-induced PAH and whether it is associated with oxidative stress. The PAH of rats was induced by MCT (60 mg/kg) and oral administration of 18β-GA (100, 50, or 25 mg/kg/day), sildenafil (30 mg/kg), or saline for 21 consecutive days. The development of PAH was evaluated by hemodynamic parameters and right ventricular hypertrophy index. Hematoxylin and eosin staining, Masson trichrome staining, and electron microscopy were used to determine the degree of vascular remodeling and proliferation in lung tissue. Moreover, the antioxidant capacity and malondialdehyde levels in the lungs were measured according to the instructions provided by the test kits, and the expression levels of nicotinamide adenine dinucleotide phosphate oxidase-2 (Nox2) and Nox4 were detected through Western blot analysis. Results of our study indicated that 18β-GA treatment significantly improved the hemodynamic and pathomorphological data of the rats, reduced the changes in oxidative stress biomarkers, and inhibited Nox2 and Nox4 expression. Our research indicated that 18β-GA has a protective effect against MCT-induced PAH by inhibiting oxidative stress in rats.